Association of blood pressure after peritoneal dialysis initiation with the decline rate of residual kidney function in newly-initiated peritoneal dialysis patients. - Yusuke Kuroki (Public Library of Science (PLoS), 2021)
Background Lower blood pressure (BP) levels are linked to a slower decline of kidney function in patients with chronic kidney disease (CKD) without kidney replacement therapy. However, there are limited data on this relation in peritoneal dialysis (PD) patients. Here we evaluated the association of BP levels with the decline of residual kidney function (RKF) in a retrospective cohort study. Methods We enrolled 228 patients whose PD was initiated between 1998 and 2014. RKF was measured as the average of creatinine and urea clearance in 24-hr urine collections. We calculated the annual decline rate of RKF by determining the regression line for individual patients. RKF is thought to decline exponentially, and thus we also calculated the annual decline rate of logarithmic scale of RKF (log RKF). We categorized the patients' BP levels at 3 months after PD initiation (BP3M) into four groups (Optimal, Normal & High normal, Grade 1 hypertension, Grade 2 & 3 hypertension) according to the 2018 European Society of Cardiology and European Society of Hypertension Guidelines for the management of arterial hypertension. Results The unadjusted, age- and sex-adjusted, and multivariable-adjusted decline rate of RKF and log RKF decreased significantly with higher BP3M levels (P for trend <0.01). Compared to those of the Optimal group, the multivariable-adjusted odds ratios (95% confidence interval) for the faster side of the median decline rate of RKF and log RKF were 4.04 (1.24-13.2) and 5.50 (1.58-19.2) in the Grade 2 and 3 hypertension group, respectively (p<0.05). Conclusions Higher BP levels after PD initiation are associated with a faster decline in RKF among PD patients.